Use the chain rule to differentiate y=(x-3)^(-3)

Hint: the chain rule states that for y=u(x) ^a, the derivative will be dy/dx = dy/du * du/dxSo we just need to find dy/du and du/dx!In this case u(x)=x-3, so du/dx = 1.from y=u^(-3), dy/du = -3u^(-4).This means we know dy/dx = -3u^(-4) * 1Converting from u to x, we get dy/dx = -3 (x-3)^(-4) .... done! 

Answered by Rosemary T. Maths tutor

4575 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Given that (cos(x)^2 + 4 sin(x)^2)/(1-sin(x)^2) = 7, show that tan(x)^2 = 3/2


Given a quadratic equation, how do I find the coordinates of the stationary point?


Find the turning points of the curve y = 3x^4 - 8x^3 -3


What is the derivative with respect to x of the function f(x)=1+x^3+ln(x), x>0 ?


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences